Virtual Screening of TADF Emitters for Single-Layer OLEDs - Lin, Kun-Han; Wetzelaer, Gert-Jan A. H.; Blom, Paul W. M.; Andrienko, Denis (Frontiers in Chemistry, 2021)
Thermally-activated delayed fluorescence (TADF) is a concept which helps to harvest triplet excitations, boosting the efficiency of an organic light-emitting diode. TADF can be observed in molecules with spatially separated donor and acceptor groups with a reduced triplet-singlet energy level splitting. TADF materials with balanced electron and hole transport are attractive for realizing efficient single-layer organic light emitting diodes, greatly simplifying their manufacturing and improving their stability. Our goal here is to computationally screen such materials and provide a comprehensive database of compounds with a range of emission wavelengths, ionization energies, and electron affinities.